Reading the Epigenetic Clock: A Comparative Analysis of DNA Methylation Markers for Age Estimation in Semen, Saliva, and Touch DNA - Febria Suryani; Bryan Helsey; Leonardo Simanjuntak; Karina Chandra; Mustafa Mahmud; Lisha Sandrina; Ahmad Erza (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: The capacity to predict an individual's age from biological evidence constitutes a significant advancement in forensic intelligence. DNA methylation, a stable epigenetic mark, provides a molecular basis for